Aneurysmal Bone Cyst of the Cervical Spine in Children: A Review and a Focus on Available Treatment Options. Issue 7 (October 2015) - Sebaaly, Amer; Ghostine, Bachir; Kreichati, Gaby; Mallet, Jean F.; Glorion, Christophe; Moussa, Ronald; Kharrat, Khalil; Ghanem, Ismat
Abstract : Objective: To present a series of pediatric cervical spine (CS) aneurysmal bone cysts (ABC), to review the literature, and to propose a treatment algorithm. Material: We present a series of 4 cases of ABC and review the literature using PubMed, EMBASE, and Google scholar. Results: Only 51 cases are documented. The mean age at diagnosis is 11.5 years, and there is a small female predominance (F:M ratio=1.6). Most of ABC occurs in the upper CS (41%), are located in the posterior component (75%), and extends in 40% of the vertebral body. A single treatment modality was used in 56.9%, whereas combination of surgery with other treatment modalities was used in the rest. Of the total number of cases, 56.8% were managed with marginal resection, and instrumentation was used in 80%. Mean follow-up was 72.5 months, with the majority of patients disease free. Pain is the most common symptom present at the latest follow-up. Conclusions: ABC of the spine is a pediatric tumor occurring rarely in the CS. Treatment options vary from simple curettage to total resection with or without instrumentation. Recurrence after surgery is highest after curettage alone. The main indications for surgery are rapid progression, despite intracystic injection, and/or the presence of neurological signs or symptoms. Level of Evidence: Level IV.